KUALITAS AIR SUNGAI DI KAWASAN WISATA PANTAI PETITENGET, KEROBOKAN KABUPATEN BADUNG BALI - Suyasa, Wayan Budiarsa; Pancadewi G. A, Sri Kunti; Suprihatin, Iryanti E.; Adi Suastuti G. A., Dwi (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 12 No 2 (2018)DO - 10.24843/EJES.2018.v12.i02.p11, 2018)
In order to maintain the environmental carrying capacity of coastal tourism, this research was conducted to determine the condition of river water environmental pollution in the Petitenget beach area and pollutant source activities. Determination of water quality is carried out by analyzing the water quality taken at several sampling points in the four rivers that lead to the Petitenget beach. Determined the pollution index value (IP) of the physical chemical and biological pollution parameters. The results showed that the four rivers that flow into the Petitenget Beach area had been contaminated with indications of pH, BOD, COD, ammonia, Coliform and E. coli which exceeded water quality category III class quality (PerGub Bali No 16 Year 2016). The four rivers are included in the criteria of severe contamination. The four rivers have experienced physical damage or structural changes that have very high discharge fluctuations both in quantity and quality. Slimy basic structure, smelly and slum aesthetic waters. While the indication of the impact of pollution is waste water which is directly discharged into the river from hotels, restaurants, homestays, commercial centers and settlements.